Brain changes following four weeks of unimanual motor training: Evidence from fMRI‐guided diffusion MRI tractography. Issue 9 (5th July 2017) - Reid, Lee B.; Sale, Martin V.; Cunnington, Ross; Mattingley, Jason B.; Rose, Stephen E.
Abstract: We have reported reliable changes in behavior, brain structure, and function in 24 healthy right‐handed adults who practiced a finger‐thumb opposition sequence task with their left hand for 10 min daily, over 4 weeks. Here, we extend these findings by using diffusion MRI to investigate white‐matter changes in the corticospinal tract, basal‐ganglia, and connections of the dorsolateral prefrontal cortex. Twenty‐three participant datasets were available with pre‐training and post‐training scans. Task performance improved in all participants (mean: 52.8%, SD: 20.0%; group P < 0.01 FWE) and widespread microstructural changes were detected across the motor system of the "trained" hemisphere. Specifically, region‐of‐interest‐based analyses of diffusion MRI ( n = 22) revealed significantly increased fractional anisotropy (FA) in the right caudate nucleus (4.9%; P < 0.05 FWE), and decreased mean diffusivity in the left nucleus accumbens (−1.3%; P < 0.05 FWE). Diffusion MRI tractography ( n = 22), seeded by sensorimotor cortex fMRI activation, also revealed increased FA in the right corticospinal tract (mean 3.28%; P < 0.05 FWE) predominantly reflecting decreased radial diffusivity. These changes were consistent throughout the entire length of the tract. The left corticospinal tract did not show any changes. FA also increased in white matter connections between the right middle frontal gyrus and both right caudate nucleus (17/22 participants; P < 0.05 FWE) and right supplementary motor area (18/22 participants; P < 0.05 FWE). Equivalent changes in FA were not seen in the left (non‐trained) hemisphere. In combination with our functional and structural findings, this study provides detailed, multifocal evidence for widespread neuroplastic changes in the human brain resulting from motor training. Hum Brain Mapp 38:4302–4312, 2017 . ©2017 Wiley Periodicals, Inc.